EVALUATION LIFETIME SERVICE AND CAPACITY OF THE KADUMALIK DAM RESERVOIR - Utamy Sukmayu Saputri; Yuli Suharnoto; Asep Sapei; Niels vuegen (Nusa Putra University, 2022)
The dam is a construction of water structures built across the river. The function of the dam is to hold and store water, both rain water, river water and water from the lake which will then form a reservoir. Kadumalik Dam is one of the projects of the Directorate General of Water Resources (SDA) of the Ministry of Public Works and Public Housing (PUPR) which will be built in 2020 on an area of 500 Ha. The purpose of building Kadumalik Dam is to meet the irrigation needs of the Irrigation Area (D.I) and meet diverse water needs, but the dam can also pose a great risk as well, namely the risk of accumulation of sedimentation. Sedimentation is one of the factors that is very influential in dam management. A large sedimentation rate will speed up the service life of the reservoir so that the planned reservoir function can be disrupted. Therefore this research is important to know how much the dam capacity and how old the dam service. This study uses analytical calculation methods for sediment transport based on observations and calculation methods with efforts to handle sedimentation. Based on the results of the analysis, the sedimentation rate in the Kadumalik Reservoir is 2.71 tons / ha / year and is classified as an erosion hazard class I or very light erosion rate, calculation of the method with sedimentation handling measures results in the analysis of the Sediment Control Building (BPS) can control 2.2 million m3 of sediment, so that it can extend the reservoir service life to 50 years.